Konseling Lintas Budaya Berbasis Pendekatan Terpadu untuk Mengatasi Kecemasan Finansial pada Mahasiswa Rantau: Studi Eksperimen Kasus Tunggal - Farrel Febriananda; Fadhilla Yusri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Migrant students who work part-time often face financial difficulties that trigger anxiety, self-blame, and emotional pressure. This study aims to examine the effectiveness of cross-cultural counseling using an integrated approach humanistic (Carl Rogers), cognitive restructuring (Aaron T. Beck), and behavioral (B.F. Skinner) in addressing financial management problems and financial anxiety in a migrant student. The method used is a Single Case Experimental Design (SCED) with an A-B design, where phase A represents the baseline condition prior to intervention and phase B represents the counseling intervention phase. The research subject is one student (initials IB), aged 20 years, a part-time worker at a motorcycle washing service while pursuing studies at UIN Sjech M. Djamil Djambek Bukittinggi. Data were collected through pre-intervention assessment interviews, behavioral observation during sessions, and post-intervention follow-up. Behavioral analysis was conducted using the Pancadaya and Likuladu-Masidu framework. Results show that following the intervention, IB was able to identify spending priorities, reduce financial anxiety, develop a simple budgeting habit, and reduce self-blaming tendencies. These findings demonstrate the effectiveness of a culturally sensitive integrated counseling approach in helping migrant students manage financial challenges.